Optimizing CSR Funds For the Economic Empowerment Community Through Islamic Financial Technology - Yusuf Agung Saputra; Nafisah Nursafanah; Khoirul Anam; Happy Sista Devy; Hendri Hermawan Adinugraha (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
The problem of poverty in Indonesia is still unfinished and this is not only the task of the government but also the concern of all stakeholders. not only a task for the government but should also be a concern for the entire community in creating economic empowerment opportunities. society in creating opportunities for economic empowerment. This research seeks to examine the optimization of CSR funds so that they can be accessed by the wider community using Islamic Financial Technology. by the wider community using Islamic Financial Technology. This research uses a literature review method with a qualitative approach. The research results in Islamic Financial Technology can be used as solution options and ideas to these problems this Fintech will be accessible to the wider community, especially rural communities that are still accessible to the wider community, especially rural communities who still do not have access to banks or are constrained by who still do not access to banks or are constrained in terms of funding. Keywords: Poverty, CSR, Islamic Financial Technology